HIV/AIDS AND DRUG PREVENTION STRATEGIES FOR THE HIGHER EDUCATION CONTEXT - Mariyani; Istiarsyah; Ardiansyah; Maisura; Zikrullah; Mena Sari (CV. Naskah Aceh, 2025)
HIV/AIDS and drug abuse are increasing in prevalence, especially among young adults, creating a public health challenge. This study aimed to improve understanding and awareness of HIV/AIDS and drug prevention among students at Muhammadiyah Mahakarya University of Aceh. A lecture was delivered to 35 students, covering key topics such as modes of HIV/AIDS transmission, prevention strategies, available treatment options, and the detrimental effects of drug abuse. It emphasized healthy behaviors and informed choices. Pre- and post-workshop assessments showed significant improvement in students' understanding, highlighting the positive impact of such interventions. This initiative contributes to preventing HIV/AIDS and drug abuse, underscoring the importance for university administrators, educators, and policymakers to invest in health education programs and incorporate them into curricula to create a supportive environment for students' health.